Network reliability evaluation of a supply chain under supplier sustainability - Lin, Kuan-Yu; Lin, Yi-Kuei (Computers & industrial engineering, 2024)
•Incorporate supplier sustainability into a multistate supply chain network (MSCN).•Apply two MCDM approaches (MEREC and TOPSIS) to determine supplier sustainability.•Evaluate network reliability while considering supplier sustainability.•Network reliability is implemented to evaluate the capability of the supply chain.•An audio production cooperation is used to demonstrate the proposed algorithm. The United Nations’ sustainable development goals have brought attention to the pressing issue of enhancing supply chain sustainability and ensuring equitable order allocation. In contrast to the previous research, this study involves sustainability in network reliability evaluation. A new algorithm is proposed for computing network reliability, the probability that the current supply chain not only meets demand, budget, and suppliers’ production capacity but also considers the level of supplier sustainability. In the constructed multistate supply chain network (MSCN), a node represents a supplier, warehouse, assembler, or market, and a route connecting the nodes represents a carrier. The capacity of each carrier, represented by the available delivery containers, should not be deterministic as they may be partially reserved by other markets. Grounded in the Method Based on the Removal Effects of Criteria (MEREC) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), the supplier sustainability can be assessed, facilitating the selection of sustainable suppliers and the determination of feasible order allocations, which are essential for various industries. An audio production cooperation is used as a case study to demonstrate the utility of the proposed algorithm.